INTERNAL FACTORS AND MACROECONOMIC FACTORS AFFECTING THE PROFITABILITY OF SHARIA INSURANCE IN INDONESIA FOR THE 2016-2018 PERIOD - Alissa Azmul Faoziyyah; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aims to examine the company's internal factors and macroeconomic factors partially and simultaneously on the profitability of islamic insurance companies in Indonesia with proxied by Return On Assets. This study uses a quantitative approach with panel data regression analysis techniques. The population of this study is sharia insurance companies in Indonesia during the period 2015-2018. The purposive sampling method is used to determine the sample used and obtained 36 Islamic insurance companies, which consist of Islamic general insurance companies and Islamic life insurance companies. The estimation results of the Fixed Effect Model with the Weighted Least Square (WLS) method show that company size, contribution growth, retakaful, leverage, investment returns, GDP and inflation simultaneously affect the profitability of islamic insurance companies in Indonesia. Partially, contributions growth and investment returns have positive and significant effect on the profitability of Islamic insurance companies in Indonesia. The variabel Company size and GDP have positive and not significant effect on the profitability of Islamic insurance in Indonesia. While the variabel leverage, retakaful, and inflation have a negative and not significant effect on the profitability of Islamic insurance companies in Indonesia. Keywords: Profitability, Islamic Insurance, Company Size, Contribution Growth, Retakaful, Leverage, Investment Results, GDP, InflationREFFERENCE Akotey, J. O., Sackey, F. G., Amoah, L., & Manson, R. F. (2013). The financial performance of life insurance companies In Ghana. The Journal of Risk Finance, 12(3), 182–194. Ali, Zainuddin. (2008). Hukum asuransi syariah. Jakarta: Sinar Grafika.Almajali, A. Y., Alamro, S. A., & Al-Soub, Y. Z. (2012). Factors affecting the financial performance of jordanian insurance companies listed at Amman Stock Exchange. Journal Of Management Research, 4(2), 266–289. Cahyadi, Ady. (2014). Mengelola hutang dalam perspektif Islam. Jurnal Bisnis dan Manajemen, 4(1), 67-7.Cahyani, Y. T. (2018). Pengaruh inflasi, Suku Bunga (BI Rate), Produk Domestik Bruto (PDB) terhadap ROA (Studi pada Bank Pembiayaan Rakyat Syariah (BPRS) di Indonesia tahun 2009-2016). Jurnal Ekonomi dan Perbankan Syariah, 5(1), 58-83.Derbali, Abdelkader. (2018). Determinants of performance of Tunisia insurance companies: Case of life insurance. International Journal of Productivity and Quality Management, 24(4), 531-541.Gujarati, Damodar N., Dan Dawn C.P. (2009). Basic econometrics. Singapore: The Mcgraw-Hill Companies Inc. Hasan, N. I. (2014). Pengantar asuransi syariah. Jakarta: Gaung Persada Press Grup.Hidayati, A. A., & Shofawati, A. (2017). Determinan kinerja keuangan asuransi syariah di Indonesia Periode 2014-2016. Jurnal Ekonomi Syariah Teori dan Terapan, 5(11), 892–907.Ismail, Noraini, dkk. (2018). Macroeconomic factors affecting performance of insurance companies in Malaysia. Academy of Accounting and Financial Studies Journal, 22(special issue), 1-5. Kaya, Emine Oner. (2015). The effect of firm-specifict factors on profitability of non-life insurance companies In Turkey. International Journal of Financial Studies, 4(4), 510-529. DOI: https://doi.org/10.3390/ijfs3040510Kramaric, T. P., Miletic, M., & Pavic, I. (2017). Profitability determinants of insurance markets in selected Central and Eastern European Countries. International Journal of Economic Sciences, 6(2), 100-123. DOI: 10.20472/ES.2017.6.2.006Lee, C. (2014). The Effects of firm specific factors and macroeconomics on profitability of property-liability insurance industry in Taiwan. Asian Economic and Financial Review, 4(5), 681–691.Malik, H. (2012). Determinants of insurance companies profitability: An analysis of insurance sector of Pakistan. Academic Research International, 1(3), 315–322.Mehari, D., & Aemiro, T. (2013). Firm specific factors that determine insurance companies’ performance in Ethiopia. European Scientific Journal April, 9(10), 245–255.Prasetyantoko, A., & Parmono, R. (2015). Does firm size matter ? An empirical study of firm performance in Indonesia. Jurnal Manajemen Bisnis, 2(2), 87–97.Sigma No.4/2010 tentang The Impact of Inflation on InsurersTulsian, M. (2014). Profitability analysis (A comparative study of Sail & Tata Steel). Journal Of Economics and Finance (Iosr-Jef), 3(2), 19–22.Widarjono, A. (2005). Ekonometrika : Teori dan aplikasi untuk ekonomi dan bisnis, edisi pertama. Yogyakarta: Ekonisia.Zulaikah. (2017). Efektivitas pengelolaan modal kerja BMT guna menjaga likuiditas dan meningkatkan profitabilitas dalam perspektif ekonomi Islam (Studi pada BMT L-RISMA Lampung Timut). Tesis tidak diterbitkan. Lampung: Institut Agama Islam Negeri Raden Intan Lampung. Zein, Firsty, D & Shofawati, Atina. (2017). Konsisi makro ekonomi terhadap hasil investasi asuransi jiwa syariah di Indonesia. Jurnal Ekonomi Syariah Teori dan Terapan, 5(10), 773-786.